SISTEM INFORMASI INVENTARISASI DENGAN IMPLEMENTASI INTERNET OF THINGS - Muslihi, Muhammad Takdir (Jurnal INSYPRO (Information System and Processing), 2024)
Traditional inventory information systems often face difficulties monitoring, real-time data maintenance, and data accuracy. This research aims to implement IoT into the inventory information system process and determine the benefits. In this research, a method called prototyping is used to create a web-based inventory information system that is integrated with IoT. The amount of product stock is measured using an ultrasonic sensor installed on the ESP8266. Sensor data is analyzed and sent to a web-based information system. allows real-time stock monitoring. The results of this IoT implementation achieve several benefits, including increased operational efficiency which can be seen from the DFD changes. The system test results show that the system can detect goods in storage with 100% accuracy